A study on the efficacy and adverse effects of methotrexate in psoriasis patients in a tertiary care centre - S., Yesodha; G., Sujatha; J., Arunkumar (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Psoriasis is a common, chronic and recurrent inflammatory disease of the skin. Methotrexate has been used in patient with psoriasis, a folic acid antagonist interfering with purine pathway and the mechanism of action in psoriasis is immune modulation and anti-inflammation. So, this study aims at monitoring the efficacy and adverse effects of methotrexate in south Indian patients with psoriasis attending a tertiary care hospital. Methods: It is a prospective, observational study conducted for a period of one year in subjects of either sex having psoriasis. Methotrexate was initiated in a single weekly oral dose of 5mg to 25mg. The efficacy was evaluated using psoriasis Area and Severity Index (PASI) score in all patients before starting methotrexate therapy and the end of first month, third month and sixth month of therapy. Adverse reaction was monitored. Results: All 40 psoriasis patients after treatment with methotrexate therapy showed improved skin lesions by falling PASI scoring at the end of first, third and sixth month of treatment. None of the patients in our study had pulmonary toxicity, life threatening adverse effects which required hospitalization. Conclusions: Use of methotrexate in the treatment of psoriasis in this study was found to be safe and highly efficacious and caused minimal adverse effects and it was well tolerated.